Teaching about social justice issues in physical education - Walton-Fisette, Jennifer L., 1978-; Sutherland, Sue; Hill, Joanne (Social issues in education., 2019)
"Addressing social justice issues in a physical education context is necessary both at the higher education and PK-12 settings. Limited undergraduate and graduate programs educate their students about social justice issues, thus, resulting in licensed teachers who lack the content knowledge, comfort level and pedagogical tools on how to educate students about issues related to social justice. Grounded in the transformative pedagogy theoretical framework, this book will offer practical lessons and strategies on a wide variety of social issues (e.g., body, race, self-identity, immigration) that can be used in teacher education and the PK-12 setting. The goal is for teacher educators and practitioners to feel more comfortable with teaching about and for social justice and believe this resource will enhance their content and pedagogical knowledge in the quest to achieve that goal. The purpose of this book is to provide physical education teacher educators and PK-12 physical education teachers with lesson plans and resources on how to address social justice issues in a physical education setting. This book will include sample lesson plans/activities that address a wide variety of social issues - the what, the how and the challenges and possibilities that the author(s) encountered when teaching such a lesson/activity. Addressing social justice issues has been limited in physical education, both in higher education and PK-12, especially in the United States. Numerous scholars, internationally, have engaged in research studies that explored how social justice issues are addressed in physical education teacher education. Although we have research to support the limitations and complexities of teaching about sociocultural issues and for social justice, a more practical resource for teacher educators and inservice teachers is needed"--